ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hamdy Hady; Linda; Febria Nalurita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the factors that influence the Dividend Policy. The sample used in this study are manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the period 2015 – 2019. The independent variables in this study are family ownership, profitability, liquidity, debt to equity ratio, sales growth, company size, independent commissioners and the dependent variable is the dividend policy which is proxied by the dividend payout ratio. The number of research samples is 44 consumer goods manufacturing companies using purposive sampling technique. The analysis model uses panel data regression analysis which is processed using E-Views software. Based on the results of panel data regression, it shows that family ownership has a significant positive effect. Profitability, liquidity, sales growth, firm size have a negative and significant effect, while the debt-to-equity ratio and independent commissioners have no effect on dividend policy. Companies should increase profitability and pay attention to company size so that they can find out how much the company is able to pay dividends. The results of this study are expected to provide input for companies and investors to consider family ownership, profitability, liquidity, debt to equity ratio, sales growth, company size, and independent commissioners because they will affect dividend policy.